Flexible code checker - Şekerci, M. Erdal. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
In software system development, the most important issue is to build a system that satisfies the requirements and works correctly. But even if a software system works correctly, this does not show that its source code is well-written. The source code may contain unnecessary codes, may have undetected bugs, or may not conform to the required coding standards or rules. This will make the code dirty and unreadable making it very difficult for other people (except the writer) to understand, update or analyze the source code. The motivation for this thesis underlies in this issue. The idea is to analyze a given source code and check it according to user defined flexible checker rules and coding standards (conventions). This could be useful in checking source codes in a variety of areas such as student projects in programming courses and deciding how good the source codes were written according to the defined rules of the checker.
Keywords: Source code (Computer science)